Extracellular Vesicle-Associated mir-21 and mir-144 Are Markedly Elevated in Serum of Patients With Hepatocellular Carcinoma - Pu, Chunwen; Huang, Hui; Wang, Zhidong; Zou, Wei; Lv, Yuecai; Zhou, Zhiyuan; Zhang, Qiqi; Qiao, Liang; Wu, Fei; Shao, Shujuan (Frontiers in Physiology, 2018)
AIM: The aim of this study was to observe the possible change of microRNAs (miRNAs) in serum extracellular vesicles (EVs) from hepatocellular carcinoma (HCC) patients. METHODS: The serum extracellular vesicles were purified from seventeen healthy donors, sixteen chronic hepatitis B (CHB) patients and twenty-four HCC patients. The sequenced microRNAs in the purified extracellular vesicles were analyzed to obtain highly differentially expressed genes (DEGs). Finally, the expression pattern of DEGs was validated using qRT-PCR. RESULTS: We found that the expression of hsa-miR-21-5p and hsa-miR-144-3p were significantly higher in extracellular vesicles and liver cancer tissues compared with serum and the distal liver tissues in HCC patients. The ratio of hsa-miR-144-3p/hsa-miR-21-5p was significantly decreased in the patients with CHB but significantly increased in patients with HCC developed from CHB (P<0.05). Hsa-144-3p/hsa-miR-21-5p exhibited greater performance than AFP (AUC 0.780, 95% CI 0.601–0.960, versus AUC 0.626, 95% CI 0.410–0.843) in ROC curve analysis. CONCLUSIONS: Extracellular vesicle-associated hsa-miR-21-5p and hsa-miR-144-3p are markedly elevated in serum of patients with hepatocellular carcinoma. The potential role of these microRNAs in the pathogenesis of HCC is worth of further study.